2018
DOI: 10.18203/2320-6012.ijrms20185386
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices regarding malaria among residents of rural Mangalore, India

Abstract: Background: Malaria is one of the most prevalent parasitic diseases worldwide and India has fourth highest number of malaria cases and deaths in the world. Prevention of the disease through better knowledge and awareness is the appropriate way to keep the disease away and remain healthy. Thus, the present study was aimed to assess the knowledge, attitude and practices regarding malaria among residents of Mangalore.Methods: Community based cross sectional study was conducted among residents in Mangalore. The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 5 publications
5
6
0
Order By: Relevance
“…It was noted in the present study that nearly all the participants (97.11%) have heard about malaria. Similar results were shown by various studies conducted by Madne et al ,[ 10 ] Gupta,[ 11 ] Borkar et al ,[ 12 ] Gupta et al ,[ 13 ] and Singh et al ,[ 14 ] where all or most of the study participants heard about malaria, whereas a study conducted by Mahesh et al . [ 15 ] in the Rural Endemic area of Kolar, India, showed that only 78% of study participants knew about malaria.…”
Section: Discussionsupporting
confidence: 87%
“…It was noted in the present study that nearly all the participants (97.11%) have heard about malaria. Similar results were shown by various studies conducted by Madne et al ,[ 10 ] Gupta,[ 11 ] Borkar et al ,[ 12 ] Gupta et al ,[ 13 ] and Singh et al ,[ 14 ] where all or most of the study participants heard about malaria, whereas a study conducted by Mahesh et al . [ 15 ] in the Rural Endemic area of Kolar, India, showed that only 78% of study participants knew about malaria.…”
Section: Discussionsupporting
confidence: 87%
“…Responses concerning the best way to cure malaria was, 50.39% of respondent said that medicine is the best way to cure, 40.31% believed that both medicine and injection are needed, only 0.78% have answered that ethnomedicine is the best way for treatment, and 1.55% have expressed that both modern medicine and traditional medicine are necessary for treatment. 6,14 Appropriate knowledge of awareness in the study is lagging, and this type of result is found by Joshi et al 12 In this study, 74.42% of respondents had a practice of cleaning the household surrounding for the prevention of malaria disease, similar results were also found by an earlier study. 15 In this study area, Dichlorodiphenyltrichloroethane (DDT) was sprayed before 3 years; it should be sprayed twice annually.…”
Section: Resultssupporting
confidence: 77%
“…60%), which is similar to the findings of previous studies [6][7][8][9][10]. Majority of respondents (89.66%) answered that tablets can cure malaria.…”
supporting
confidence: 89%
See 2 more Smart Citations